Cancer screening in New Zealand. (March 2020) - O'Hallahan, Jane; Church, Emma; Shaw, Caroline
Highlights: New Zealand's National Screening Unit coordinates three national cancer screening programmes - cervical, breast and bowel screening. The National Bowel Screening Programme is currently being rolled out across the country with full implementation expected by the end of 2021. A key challenge for the screening programmes is achieving access and outcome equity for all population groups, particularly Mâori and Pacific. An equity promoting strategy under consideration is for Mâori to start bowel screening from 50 years compared to 60 years for other groups. Abstract: New Zealand's organised cancer screening programmes are managed by a specialist unit within the New Zealand Ministry of Health. Advice on new screening programmes is provided by an independent advisory group, although decisions on funding and implementation remain political. New Zealand currently has three organised cancer screening programmes; BreastScreen Aotearoa, the National Cervical Screening Programme and the National Bowel Screening Programme. The key challenges for cancer screening in New Zealand are achieving equitable outcomes for different population groups, the difficulties changing an existing or implementing a new screening programme, and the complexity of facilitating informed consent. New Zealand has a particular focus on achieving equity in cancer screening for Māori, the indigenous population of New Zealand, with specific initiatives being considered at a range of levels to increase coverage and change programme parameters.